Addition type thermocuring organic silicon pressure-sensitive adhesive and preparation method thereof
By mixing component A, component B and component C, and using addition reaction catalyzed by chloroplatinic acid, an addition-cured silicone pressure-sensitive adhesive was prepared, which solved the problems of low mechanical strength and poor bonding effect in the prior art, and achieved higher mechanical strength and bonding effect.
Patent Information
- Application Number
- CN202510040416.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The current addition-shaped silicone pressure-sensitive adhesive has low mechanical strength and poor bonding effect, resulting in structural failure.
By mixing component A, component B and component C, an addition-shaped heat-cured silicone pressure-sensitive adhesive is prepared. Component A includes methyl vinyl MQ resin, reinforced crosslinking agent, modified filler and ethyl acetate, component B includes hydrogen-containing silicone oil and m-phenylenediamine, and component C is chloroplatinic acid. The reinforced crosslinking agent is made through multiple reactions, and the modified filler is made by carbon nanotube treatment, and it is catalyzed by chloroplatinic acid to add reaction at high temperature to form a crosslinking structure.
It improves the mechanical strength and bonding effect of silicone pressure-sensitive adhesive, enhances its toughness and wear resistance, and improves the stability of the structure.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of organic silicon pressure-sensitive adhesive, and in particular to an addition-type heat-curing organic silicon pressure-sensitive adhesive and a preparation method thereof. Background Art
[0002] Pressure-sensitive adhesive is a type of adhesive that is sensitive to pressure and is widely used in packaging, labeling, electrical insulation, medical and health care, and honeycomb cutting and positioning. Among them, silicone pressure-sensitive adhesive, as a special pressure-sensitive adhesive material, has excellent properties such as high and low temperature resistance, UV resistance, and moisture resistance, and also has good adhesion to low surface energy materials such as polytetrafluoroethylene and silicone rubber. Molded thermosetting silicone pressure-sensitive adhesive mainly uses platinum as a catalyst to graft vinyl-containing and silicon-hydrogen bond-containing polysiloxanes together through a silylation reaction to form a new silicon-carbon bond, and cross-linking and vulcanization will form a new three-dimensional network structure. Its main components include base polymers, crosslinking agents (including silicone oil), platinum catalysts, inhibitors, and reinforcing fillers. At this stage, the addition-type silicone pressure-sensitive adhesive has insufficient mechanical strength and poor bonding effect, which leads to structural failure. Summary of the invention
[0003] The purpose of the present invention is to provide an addition type heat curing organosilicon pressure sensitive adhesive and a preparation method thereof, so as to solve the problem of low mechanical strength of organosilicon pressure sensitive adhesive at present stage. The purpose of the present invention can be achieved through the following technical solutions: A method for preparing an addition-type heat-curing silicone pressure-sensitive adhesive comprises the following steps: Component A, component B and component C are mixed to prepare an addition-type heat-curing silicone pressure-sensitive adhesive, wherein component A comprises the following raw materials in parts by weight: 10-20 parts of methyl vinyl MQ resin, 8-10 parts of reinforcing crosslinking agent, 2-5 parts of modified filler and 4-6 parts of ethyl acetate, component B comprises the following raw materials in parts by weight: 3-5 parts of hydrogenated silicone oil and 3-5 parts of meta-phenylenediamine, and component C comprises the following raw materials in parts by weight: 3-5 parts of chloroplatinic acid.
[0004] Further, the reinforcing cross-linking agent is prepared by the following steps: Step B1: Ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF are mixed, and the mixture is reacted at a speed of 200-300 r / min and a temperature of 0°C for 2-3 hours to obtain intermediate 1; 3-chloropropyldimethylmethoxysilane, maleimide, potassium hydroxide and DMF are mixed, nitrogen is introduced for protection, and the mixture is reacted at a speed of 150-200 r / min and a temperature of 35-40°C for 1-1.5 hours to obtain intermediate 2; Step B2: The intermediate 1, the intermediate 2, triethylamine and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 160-165° C. to obtain a modified monomer; octamethylcyclotetrasiloxane, the modified monomer, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed evenly, and the reaction is carried out for 2-3 hours at a speed of 150-200 r / min and a temperature of 105-110° C. to obtain a diamine-terminated polysiloxane; Step B3: Mix diamine-terminated polysiloxane, dehydrated glyceryl methacrylate and DMF evenly, and react for 3-5 hours at a speed of 150-200 r / min, a temperature of 50-60°C, and a pH value of 11-12 to obtain intermediate 3. Mix intermediate 3, epichlorohydrin and DMF, stir and add boron trifluoride at a speed of 120-150 r / min and a temperature of 65-70°C, react for 2-3 hours, add sodium hydroxide solution, heat to 75-80°C, and continue to react for 3-5 hours to obtain a reinforcing cross-linking agent.
[0005] Furthermore, the amount ratio of ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF in step B1 is 1 g:4 g:0.7 g:1 mL:50 mL, and the molar ratio of 3-chloropropyldimethylmethoxysilane, maleimide and potassium hydroxide is 1:1:1.2.
[0006] Furthermore, the molar ratio of intermediate 1 and intermediate 2 in step B2 is 1:2, the amount of triethylamine used is 2% of the mass of intermediate 1, and the molar ratio of octamethylcyclotetrasiloxane, modified monomer, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1.8:0.6:2:3.
[0007] Furthermore, the molar ratio of the diamine-terminated polysiloxane and dehydrated glyceryl methacrylate described in step B3 is 1:4, the amount ratio of intermediate 3, epichlorohydrin, boron trifluoride and hydroxide solution is 10mL:40mL:0.9g:5mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0008] Further, the modified filler is prepared by the following steps: Step C1: mixing carbon nanotubes and mixed acid, reacting for 3-5 hours at a speed of 60-80 r / min and a temperature of 100-110° C., washing with deionized water until neutral to obtain pretreated carbon nanotubes, dispersing the pretreated carbon nanotubes in ethanol, stirring and adding deionized water and KH550 at a speed of 200-300 r / min and a temperature of 70-80° C., reacting for 2-3 hours, and obtaining modified carbon nanotubes; Step C2: Modified carbon nanotubes, p-formylstyrene, p-toluenesulfonic acid and DMF are mixed, and the mixture is reacted for 3-5 hours at a rotation speed of 200-300 r / min and a temperature of 50-60° C. to obtain functionalized carbon nanotubes; functionalized carbon nanotubes, divinylbenzene, dehydrated glyceryl methacrylate and acetonitrile are mixed evenly, nitrogen is introduced for protection, azobisisobutyronitrile is added under stirring at a rotation speed of 200-300 r / min and a temperature of 70-75° C., and the mixture is reacted for 8-10 hours to obtain modified fillers.
[0009] Furthermore, the amount ratio of the carbon nanotubes and the mixed acid in step C1 is 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the amount of KH550 used is 3% of the mass of the pretreated carbon nanotubes.
[0010] Furthermore, the molar ratio of amino groups on the modified carbon nanotubes and p-formylstyrene in step C2 is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of p-formylstyrene, and the mass ratio of functionalized carbon nanotubes, divinylbenzene and methacrylic acid dehydrated glyceryl ether is 1:6:10.
[0011] Beneficial effects of the present invention: The addition-type heat-curing organic silicone pressure-sensitive adhesive disclosed in the present invention is prepared by mixing component A, component B and component C, wherein component A comprises the following raw materials: methyl vinyl MQ resin, a reinforcing crosslinking agent, a modified filler and ethyl acetate, component B comprises the following raw materials: hydrogen-containing silicone oil and metaphenylenediamine, and component C is chloroplatinic acid.
[0012] The reinforcing crosslinking agent is reacted with ethylene glycol and furanoyl chloride as raw materials, so that the alcohol hydroxyl group on the ethylene glycol reacts with the acyl chloride on the furanoyl chloride to obtain intermediate 1, 3-chloropropyldimethylmethoxysilane and maleimide react, so that the chlorine atom site on the 3-chloropropyldimethylmethoxysilane reacts with the imine on the maleimide to obtain intermediate 2, intermediate 1 and intermediate 2 are reacted under the action of triethylamine, so that the furanyl on intermediate 1 reacts with the maleimide DA on intermediate 2 to obtain a modified monomer, and octamethylcyclotetrasiloxane is reacted with octamethylcyclotetrasiloxane. The product is ring-opened, polymerized with a modified monomer, and finally terminated with 1,3-bis(3-aminopropyl)tetramethyldisiloxane to obtain a diamine-terminated polysiloxane. The diamine-terminated polysiloxane is reacted with dehydrated glyceryl methacrylate to react the amino group on the diamine-terminated polysiloxane with the epoxy group on glycidyl methacrylate to form a new hydroxyl group to obtain intermediate 3. The intermediate 3 is reacted with epichlorohydrin to react the hydroxyl group on intermediate 3 with the epoxy group on epichlorohydrin, and then the ring is closed under the action of sodium hydroxide solution to form a new epoxy group to obtain a reinforcing crosslinking agent.
[0013] The modified filler is prepared by treating carbon nanotubes as raw materials with mixed acid so that active groups are grafted onto the surfaces of the carbon nanotubes to obtain pretreated carbon nanotubes. The pretreated carbon nanotubes are treated with KH550 so that amino groups are grafted onto the surfaces to obtain modified carbon nanotubes. The modified carbon nanotubes are reacted with p-formylstyrene so that the amino groups on the modified carbon nanotubes react with the aldehyde groups on the p-formylstyrene to obtain functionalized carbon nanotubes. The functionalized carbon nanotubes, divinylbenzene and dehydrated glycerol methacrylate are polymerized and the surfaces of the modified carbon nanotubes are coated with polymers to obtain modified fillers.
[0014] After component A, component B and component C are blended and heated at high temperature, the double bonds on the methyl vinyl MQ resin and the double bonds on the reinforcing cross-linking agent will react with the Si-H bonds on the hydrogen-containing silicone oil through the action of chloroplatinic acid. At the same time, under the action of meta-phenylenediamine, the epoxy group on the reinforcing cross-linking agent and the epoxy group on the surface of the modified filler also react, so that cross-linking occurs between the methyl vinyl MQ resin, the reinforcing cross-linking agent, the hydrogen-containing silicone oil and the modified filler, thereby improving the mechanical strength of the pressure-sensitive adhesive. The modified filler has a core-shell structure of a hard core and a soft shell, and the inner core and the outer shell contain an imine bond and a lactone ring in the reinforcing cross-linking agent, which can further improve the toughness of the pressure-sensitive adhesive. DETAILED DESCRIPTION
[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] Embodiment 1: A method for preparing an addition-type heat-curing silicone pressure-sensitive adhesive, comprising the following steps: Component A, component B and component C are mixed to prepare an addition-type heat-curing silicone pressure-sensitive adhesive. Component A includes the following raw materials in parts by weight: 10 parts of methyl vinyl MQ resin, 8 parts of reinforcing cross-linking agent, 2 parts of modified filler and 4 parts of ethyl acetate. Component B includes the following raw materials in parts by weight: 3 parts of hydrogenated silicone oil and 3 parts of meta-phenylenediamine. Component C includes the following raw materials in parts by weight: 3 parts of chloroplatinic acid.
[0017] The model of the methyl vinyl MQ resin is DY-VMQ101, and the model of the hydrogen-containing silicone oil is RH-H502.
[0018] The reinforcing cross-linking agent is prepared by the following steps: Step B1: Ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 200 r / min and a temperature of 0°C for 2 h to obtain intermediate 1; 3-chloropropyldimethylmethoxysilane, maleimide, potassium hydroxide and DMF were mixed, nitrogen was introduced for protection, and the mixture was reacted at a speed of 150 r / min and a temperature of 35°C for 1 h to obtain intermediate 2; Step B2: The intermediate 1, the intermediate 2, the triethylamine and the DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 160° C. to obtain a modified monomer; octamethylcyclotetrasiloxane, the modified monomer, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed evenly, and the reaction is carried out for 2 hours at a speed of 150 r / min and a temperature of 105° C. to obtain a diamine-terminated polysiloxane; Step B3: Mix diamine-terminated polysiloxane, dehydrated glyceryl methacrylate and DMF evenly, and react for 3 hours at a speed of 150 r / min, a temperature of 50°C and a pH value of 11 to obtain intermediate 3. Mix intermediate 3, epichlorohydrin and DMF, stir and add boron trifluoride at a speed of 120 r / min and a temperature of 65°C, react for 2 hours, add sodium hydroxide solution, raise the temperature to 75°C, and continue to react for 3 hours to obtain a reinforcing cross-linking agent.
[0019] The amount ratio of ethylene glycol, furanyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step B1 is 1g:4g:0.7g:1mL:50mL, and the molar ratio of 3-chloropropyldimethylmethoxysilane, maleimide and potassium hydroxide is 1:1:1.2.
[0020] The molar ratio of intermediate 1 and intermediate 2 described in step B2 is 1:2, the amount of triethylamine used is 2% of the mass of intermediate 1, and the molar ratio of octamethylcyclotetrasiloxane, modified monomer, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1.8:0.6:2:3.
[0021] The molar ratio of the diamine-terminated polysiloxane and dehydrated glyceryl methacrylate described in step B3 is 1:4, the amount ratio of intermediate 3, epichlorohydrin, boron trifluoride and hydroxide solution is 10mL:40mL:0.9g:5mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0022] The modified filler is prepared by the following steps: Step C1: mixing carbon nanotubes and mixed acid, reacting for 3 hours at a speed of 60 r / min and a temperature of 100° C., washing with deionized water until neutral to obtain pretreated carbon nanotubes, dispersing the pretreated carbon nanotubes in ethanol, stirring and adding deionized water and KH550 at a speed of 200 r / min and a temperature of 70° C., reacting for 2 hours to obtain modified carbon nanotubes; Step C2: Modified carbon nanotubes, p-formylstyrene, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 50°C to obtain functionalized carbon nanotubes. Functionalized carbon nanotubes, divinylbenzene, dehydrated glyceryl methacrylate and acetonitrile are mixed evenly, nitrogen is introduced for protection, azobisisobutyronitrile is added under stirring at a speed of 200 r / min and a temperature of 70°C, and the reaction is carried out for 8 hours to obtain modified fillers.
[0023] The amount ratio of the carbon nanotubes and the mixed acid in step C1 is 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the amount of KH550 used is 3% of the mass of the pretreated carbon nanotubes.
[0024] The molar ratio of amino groups on the modified carbon nanotubes and p-formylstyrene described in step C2 is 1:1, the amount of p-toluenesulfonic acid used is 1% of the mass of p-formylstyrene, and the mass ratio of functionalized carbon nanotubes, divinylbenzene and methacrylic acid dehydrated glycerol ether is 1:6:10.
[0025] Embodiment 2: A method for preparing an addition-type heat-curing silicone pressure-sensitive adhesive, comprising the following steps: Component A, component B and component C are mixed to prepare an addition-type heat-curing silicone pressure-sensitive adhesive, wherein component A comprises the following raw materials in parts by weight: 15 parts of methyl vinyl MQ resin, 9 parts of reinforcing cross-linking agent, 3.5 parts of modified filler and 5 parts of ethyl acetate, component B comprises the following raw materials in parts by weight: 4 parts of hydrogenated silicone oil and 4 parts of meta-phenylenediamine, and component C comprises the following raw materials in parts by weight: 4 parts of chloroplatinic acid.
[0026] The model of the methyl vinyl MQ resin is DY-VMQ101, and the model of the hydrogen-containing silicone oil is RH-H502.
[0027] The reinforcing cross-linking agent is prepared by the following steps: Step B1: Ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 200 r / min and a temperature of 0°C for 3 h to obtain intermediate 1; 3-chloropropyldimethylmethoxysilane, maleimide, potassium hydroxide and DMF were mixed, and nitrogen was introduced for protection, and the mixture was reacted at a speed of 150 r / min and a temperature of 40°C for 1.3 h to obtain intermediate 2; Step B2: The intermediate 1, the intermediate 2, triethylamine and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 165° C. to obtain a modified monomer; octamethylcyclotetrasiloxane, the modified monomer, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed evenly, and the reaction is carried out for 2 hours at a speed of 150 r / min and a temperature of 110° C. to obtain a diamine-terminated polysiloxane; Step B3: Mix diamine-terminated polysiloxane, dehydrated glyceryl methacrylate and DMF evenly, and react for 4 hours at a speed of 200 r / min, a temperature of 55°C and a pH value of 12 to obtain intermediate 3. Mix intermediate 3, epichlorohydrin and DMF, stir and add boron trifluoride at a speed of 120 r / min and a temperature of 70°C, react for 2 hours, add sodium hydroxide solution, raise the temperature to 80°C, and continue to react for 4 hours to obtain a reinforcing cross-linking agent.
[0028] The amount ratio of ethylene glycol, furanyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step B1 is 1g:4g:0.7g:1mL:50mL, and the molar ratio of 3-chloropropyldimethylmethoxysilane, maleimide and potassium hydroxide is 1:1:1.2.
[0029] The molar ratio of intermediate 1 and intermediate 2 described in step B2 is 1:2, the amount of triethylamine used is 2% of the mass of intermediate 1, and the molar ratio of octamethylcyclotetrasiloxane, modified monomer, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1.8:0.6:2:3.
[0030] The molar ratio of the diamine-terminated polysiloxane and dehydrated glyceryl methacrylate described in step B3 is 1:4, the amount ratio of intermediate 3, epichlorohydrin, boron trifluoride and hydroxide solution is 10mL:40mL:0.9g:5mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0031] The modified filler is prepared by the following steps: Step C1: mixing carbon nanotubes and mixed acid, reacting for 4 hours at a speed of 60 r / min and a temperature of 105° C., washing with deionized water to neutrality to obtain pretreated carbon nanotubes, dispersing the pretreated carbon nanotubes in ethanol, stirring and adding deionized water and KH550 at a speed of 200 r / min and a temperature of 75° C., and reacting for 3 hours to obtain modified carbon nanotubes; Step C2: Modified carbon nanotubes, p-formylstyrene, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 60°C to obtain functionalized carbon nanotubes. Functionalized carbon nanotubes, divinylbenzene, dehydrated glyceryl methacrylate and acetonitrile are mixed evenly, nitrogen is introduced for protection, azobisisobutyronitrile is added under stirring at a speed of 200 r / min and a temperature of 75°C, and the reaction is carried out for 9 hours to obtain modified fillers.
[0032] The amount ratio of the carbon nanotubes and the mixed acid in step C1 is 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the amount of KH550 used is 3% of the mass of the pretreated carbon nanotubes.
[0033] The molar ratio of amino groups on the modified carbon nanotubes and p-formylstyrene described in step C2 is 1:1, the amount of p-toluenesulfonic acid used is 1% of the mass of p-formylstyrene, and the mass ratio of functionalized carbon nanotubes, divinylbenzene and methacrylic acid dehydrated glycerol ether is 1:6:10.
[0034] Embodiment 3: A method for preparing an addition-type heat-curing silicone pressure-sensitive adhesive, comprising the following steps: Component A, component B and component C are mixed to prepare an addition-type heat-curing silicone pressure-sensitive adhesive, wherein component A comprises the following raw materials in parts by weight: 20 parts of methyl vinyl MQ resin, 10 parts of reinforcing crosslinking agent, 5 parts of modified filler and 6 parts of ethyl acetate, component B comprises the following raw materials in parts by weight: 5 parts of hydrogenated silicone oil and 3-5 parts of meta-phenylenediamine, and component C comprises the following raw materials in parts by weight: 5 parts of chloroplatinic acid.
[0035] The model of the methyl vinyl MQ resin is DY-VMQ101, and the model of the hydrogen-containing silicone oil is RH-H502.
[0036] The reinforcing cross-linking agent is prepared by the following steps: Step B1: Ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and the mixture was reacted at a speed of 300 r / min and a temperature of 0°C for 3 h to obtain intermediate 1; 3-chloropropyldimethylmethoxysilane, maleimide, potassium hydroxide and DMF were mixed, nitrogen was introduced for protection, and the mixture was reacted at a speed of 200 r / min and a temperature of 40°C for 1.5 h to obtain intermediate 2; Step B2: The intermediate 1, the intermediate 2, triethylamine and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 165° C. for 5 hours to obtain a modified monomer; octamethylcyclotetrasiloxane, the modified monomer, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane were mixed evenly, and the reaction was carried out at a speed of 200 r / min and a temperature of 110° C. for 3 hours to obtain a diamine-terminated polysiloxane; Step B3: Mix diamine-terminated polysiloxane, dehydrated glyceryl methacrylate and DMF evenly, and react for 5 hours at a speed of 200 r / min, a temperature of 60°C and a pH value of 12 to obtain intermediate 3. Mix intermediate 3, epichlorohydrin and DMF, stir and add boron trifluoride at a speed of 150 r / min and a temperature of 70°C, react for 3 hours, add sodium hydroxide solution, raise the temperature to 80°C, and continue to react for 5 hours to obtain a reinforcing cross-linking agent.
[0037] The amount ratio of ethylene glycol, furanyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step B1 is 1g:4g:0.7g:1mL:50mL, and the molar ratio of 3-chloropropyldimethylmethoxysilane, maleimide and potassium hydroxide is 1:1:1.2.
[0038] The molar ratio of intermediate 1 and intermediate 2 described in step B2 is 1:2, the amount of triethylamine used is 2% of the mass of intermediate 1, and the molar ratio of octamethylcyclotetrasiloxane, modified monomer, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1.8:0.6:2:3.
[0039] The molar ratio of the diamine-terminated polysiloxane and dehydrated glyceryl methacrylate described in step B3 is 1:4, the amount ratio of intermediate 3, epichlorohydrin, boron trifluoride and hydroxide solution is 10mL:40mL:0.9g:5mL, and the mass fraction of the sodium hydroxide solution is 25%.
[0040] The modified filler is prepared by the following steps: Step C1: mixing carbon nanotubes and mixed acid, reacting for 5 hours at a speed of 80 r / min and a temperature of 110° C., washing with deionized water to neutrality to obtain pretreated carbon nanotubes, dispersing the pretreated carbon nanotubes in ethanol, stirring and adding deionized water and KH550 at a speed of 300 r / min and a temperature of 80° C., reacting for 3 hours to obtain modified carbon nanotubes; Step C2: Modified carbon nanotubes, p-formylstyrene, p-toluenesulfonic acid and DMF are mixed, and the reaction is carried out for 5 hours at a rotation speed of 300 r / min and a temperature of 60°C to obtain functionalized carbon nanotubes. Functionalized carbon nanotubes, divinylbenzene, dehydrated glyceryl methacrylate and acetonitrile are mixed evenly, nitrogen is introduced for protection, and azobisisobutyronitrile is added under stirring at a rotation speed of 300 r / min and a temperature of 75°C, and the reaction is carried out for 10 hours to obtain modified fillers.
[0041] The amount ratio of the carbon nanotubes and the mixed acid in step C1 is 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the amount of KH550 used is 3% of the mass of the pretreated carbon nanotubes.
[0042] The molar ratio of amino groups on the modified carbon nanotubes and p-formylstyrene described in step C2 is 1:1, the amount of p-toluenesulfonic acid used is 1% of the mass of p-formylstyrene, and the mass ratio of functionalized carbon nanotubes, divinylbenzene and methacrylic acid dehydrated glycerol ether is 1:6:10.
[0043] Comparative Example 1: Compared with Example 1, no modified monomer was added to this comparative example, and the remaining steps were the same.
[0044] Comparative Example 2: Compared with Example 1, this comparative example uses intermediate 3 instead of the reinforcing cross-linking agent, and the remaining steps are the same.
[0045] Comparative Example 3: Compared with Example 1, this comparative example uses carbon nanotubes instead of functionalized carbon nanotubes, and the remaining steps are the same.
[0046] The surface hardness of the pressure-sensitive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to the standard of GB / T531.1-2008, with a sample thickness of 6 mm. The shear strength was tested according to the standard of GB / T13936-2014. The thickness of the PC substrate and the pressure-sensitive adhesive was uniformly 2 mm. The tensile strength was tested according to the standard of GB / T528-2009, with the sample being a Type 3 dumbbell. The test results are shown in Table 1 below.
[0047] Table 1
[0048] It can be seen from the above table that the present application has good adhesion and mechanical strength.
[0049] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an addition-type heat-curing silicone pressure-sensitive adhesive, characterized in that: The specific steps include: Component A, component B and component C are mixed to prepare an addition-type heat-curing silicone pressure-sensitive adhesive, wherein component A comprises the following raw materials in parts by weight: 10-20 parts of methyl vinyl MQ resin, 8-10 parts of reinforcing crosslinking agent, 2-5 parts of modified filler and 4-6 parts of ethyl acetate, component B comprises the following raw materials in parts by weight: 3-5 parts of hydrogenated silicone oil and 3-5 parts of meta-phenylenediamine, and component C comprises the following raw materials in parts by weight: 3-5 parts of chloroplatinic acid.
2. The method for preparing an addition type heat-curing silicone pressure-sensitive adhesive according to claim 1, characterized in that: The reinforcing cross-linking agent is prepared by the following steps: Step B1: Ethylene glycol, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF are mixed and reacted to obtain intermediate 1; 3-chloropropyldimethylmethoxysilane, maleimide, potassium hydroxide and DMF are mixed and nitrogen is passed through to react to obtain intermediate 2; Step B2: The intermediate 1, the intermediate 2, triethylamine and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain a modified monomer, and octamethylcyclotetrasiloxane, the modified monomer, tetramethylammonium hydroxide, tetrahydrofuran and 1,3-bis(3-aminopropyl)tetramethyldisiloxane are mixed for reaction to obtain a diamine-terminated polysiloxane; Step B3: diamine-terminated polysiloxane, dehydrated methacrylate and DMF are mixed and reacted to obtain intermediate 3, intermediate 3, epichlorohydrin and DMF are mixed and stirred, and boron trifluoride is added. After the reaction, sodium hydroxide solution is added, and the temperature is raised to continue the reaction to obtain a reinforcing crosslinking agent.
3. The method for preparing an addition type heat-curing silicone pressure-sensitive adhesive according to claim 2, characterized in that: The amount ratio of ethylene glycol, furanyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step B1 is 1g:4g:0.7g:1mL:50mL, and the molar ratio of 3-chloropropyldimethylmethoxysilane, maleimide and potassium hydroxide is 1:1:1.
2.
4. The method for preparing an addition type heat-curing organosilicon pressure-sensitive adhesive according to claim 2, characterized in that: The molar ratio of intermediate 1 and intermediate 2 in step B2 is 1:2, and the molar ratio of octamethylcyclotetrasiloxane, modified monomer, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)tetramethyldisiloxane is 1.8:0.6:2:
3.
5. The method for preparing an addition type heat-curing silicone pressure-sensitive adhesive according to claim 2, characterized in that: The molar ratio of the diamine-terminated polysiloxane and dehydrated methacrylate described in step B3 is 1:4, and the amount ratio of intermediate 3, epichlorohydrin, boron trifluoride and hydroxide solution is 10mL:40mL:0.9g:5mL.
6. The method for preparing an addition type heat-curing organosilicon pressure-sensitive adhesive according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step C1: After the carbon nanotubes and the mixed acid are mixed and reacted, the mixture is washed with deionized water until it becomes neutral to obtain pretreated carbon nanotubes, the pretreated carbon nanotubes are dispersed in ethanol, and deionized water and KH550 are added and stirred to react to obtain modified carbon nanotubes; Step C2: the modified carbon nanotubes, p-formylstyrene, p-toluenesulfonic acid and DMF are mixed and reacted to obtain functionalized carbon nanotubes; the functionalized carbon nanotubes, divinylbenzene, dehydrated glyceryl methacrylate and acetonitrile are evenly mixed, nitrogen is introduced for protection, azobisisobutyronitrile is added and stirred to react to obtain a modified filler.
7. The method for preparing an addition type heat-curing organosilicon pressure-sensitive adhesive according to claim 6, characterized in that: The amount ratio of the carbon nanotubes and the mixed acid in step C1 is 1 g:80 mL, the mixed acid is prepared by mixing concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, and the amount of KH550 used is 3% of the mass of the pretreated carbon nanotubes.
8. The method for preparing an addition type heat-curing organosilicon pressure-sensitive adhesive according to claim 6, characterized in that: The molar ratio of the amino groups on the modified carbon nanotubes and p-formylstyrene in step C2 is 1:1, and the mass ratio of the functionalized carbon nanotubes, divinylbenzene and methacrylic acid dehydrated glycerol ether is 1:6:
10.
9. An addition type heat-curing silicone pressure-sensitive adhesive, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.